Pengaruh Persepsi Mengenai Harapan Orang Tua terhadap Career Decision Making Self Efficacy pada Siswa SMA Negeri Kelas XII di Kota Bandung - Farizi Raka Pradipa; Temi Damayanti Djamhoer (Bandung Conference Series: Psychology Science, 2022)
Abstract. Problems in determining a career at the high school education level are still experienced by students. Based on the survey data found, 92% of high school students are still confused and undecided whether they will continue their education level or start their career immediately. The conditions experienced by high school students can cause problems when they start entering the next level of education, namely college. This is evidenced by the survey data found, namely 87% of Indonesian students feel that the majors taken in college are not in accordance with their interests. One of the factors is the difference in the wishes of their parents when they were in high school. Seeing the involvement of parents' desires in determining career choices, this study aims to examine the effect of perceptions of parental expectations on career decision making self-efficacy in public high school. The research method used in this study is non-experimental causality with a quantitative approach. The subjects of this study were 273 students in grade 12th at public high school in Bandung. This research uses two measuring instruments namely, Perception of Parental Expectations Inventory and Career Decision Making Self Efficacy Scale – Short Form. The data analysis of this research used simple linear regression analysis. The results obtained from this study are that there is an influence of perceptions of parents' expectations on career decision making self-efficacy, with an effect of 24.9%. Abstrak. Masalah dalam menentukan karir pada jenjang pendidikan SMA masih dialami oleh siswa. Berdasarkan data yang ditemukan yaitu sebanyak 92% siswa SMA sederajat masih mengalami kebingungan dan ragu apakah mereka akan melanjutkan jenjang pendidikan selanjutnya atau langsung memulai karir. Kondisi yang dialami siswa SMA ini dapat memunculkan masalah apabila mereka mulai memasuki jenjang pendidikan selanjutnya yaitu perguruan tinggi. Hal ini dibuktikan dengan salah satu data yang ditemukan yaitu sebanyak 87% mahasiswa Indonesia mengakui bahwa jurusan yang diambil diperkuliahan tidak sesuai dengan minatnya. Salah satu faktor yaitu adanya perbedaan keinginan orang tua ketika mereka di SMA. Melihat adanya keterlibatan keinginan orang tua dalam menentukan pilihan karir, sehingga penelitian ini bertujuan untuk menguji pengaruh persepsi mengenai harapan orang tua terhadap career decision making self-efficacy pada siswa SMA Negeri Kelas XII di Kota Bandung. Metode penelitian yang digunakan pada penelitian ini adalah kausalitas non eksperimental dengan pendekatan kuantitatif. Subjek dalam penelitian ini adalah siswa SMA Negeri Kelas XII di Kota Bandung sebanyak 273 siswa. Penelitian ini menggunakan alat ukur Perception of Parental Expectations Inventory dan Career Decision Making Self Efficacy Scale – Short Form. Analisis data penelitian ini menggunakan analisis regresi linier sederhana. Hasil yang didapatkan dari penelitian ini adalah terdapat pengaruh persepsi mengenai harapan orang tua terhadap career decison making self-efficacy, dengan pengaruhnya sebanyak 24,9 %.